Numerical Study on Interaction between Submarine Landslides and a Monopile Using CFD Techniques - Ru-Yu Li; Jin-Jian Chen; Chen-Cong Liao (Journal of Marine Science and Engineering, 2021)
Offshore installations with pile foundations in shallow water are vulnerable to submarine landslides, which cause serious damage to engineering facilities, loss of life, and loss of money. Due to a shortage of real observation data and the difficulty of reproduction, we lack insight into the interaction behavior between submarine landslides and monopiles. This study capitalized on ANSYS Fluent 20.0 to develop a three-dimensional biphasic (water and slurry) numerical model. This CFD model was used to analyze the interaction between a monopile and submarine landslides at different flow heights. The velocities of submarine landslides were from low to high values. Two modes of interactional forces acting on the monopile are proposed, which are (i) interaction force with peak value and (ii) interaction force without peak value. The influence of flow height and velocity on interaction forces was investigated. Results show that the effect of the flow heights on the interaction force is significant at low velocity stage, while the peak force representing a hazard level of the pile was non-negligible under high flow velocity and low flow height conditions, which should be considered in a future study. The related mechanisms are revealed with a hybrid model considering different components of the force.